Tuning superconductivity in twisted bilayer graphene - Yankowitz, Matthew; Chen, Shaowen; Polshyn, Hryhoriy; Zhang, Yuxuan; Watanabe, K.; Taniguchi, T.; Graf, David; Young, Andrea F.; Dean, Cory R. (Science (American Association for the Advancement of Science), 2019)
Materials with flat electronic bands often exhibit exotic quantum phenomena owing to strong correlations. An isolated low-energy flat band can be induced in bilayer graphene by simply rotating the layers by 1.1°, resulting in the appearance of gate-tunable superconducting and correlated insulating phases. In this study, we demonstrate that in addition to the twist angle, the interlayer coupling can be varied to precisely tune these phases. We induce superconductivity at a twist angle larger than 1.1°—in which correlated phases are otherwise absent—by varying the interlayer spacing with hydrostatic pressure. Our low-disorder devices reveal details about the superconducting phase diagram and its relationship to the nearby insulator. Our results demonstrate twisted bilayer graphene to be a distinctively tunable platform for exploring correlated states.